Business cycles - Peter Skott (University of Massachusetts, Department of Economics, 2011)
This note outlines and discusses some of the strands in the post-Keynesian literature on business cycles. Most post-Keynesians have focused on endogenously generated cycles, but the mechanism varies: some focus on the goods market, others on financial markets, the labor market, or political intervention. The merits of formal modeling of the cycles have also come in for debate.
Keywords: 330